Level of Poverty in Cities and Regencies - Sri Nathasya Br Sitepu (Universitas Gorontalo, 2023)
This study analyzes the poverty rate of regencies/cities on the island of Sumatra using quantitative methodology. Panel data regression analysis techniques with Pooled least Square (PLS), Fixed Effect Model (FEM), and Random Effect Model (REM). The panel data in the study is a combination of time series data for 2010-2019 with cross-section data from 153 regencies/cities on the island of Sumatra. The purpose of the study was to find the best panel data regression model and determine the variables that affect the poverty rate of regencies/cities on the island of Sumatra. The results of the research analysis found a fixed effect model (FEM) as the best model for analyzing the poverty rate (P0) of regencies/cities on the island of Sumatra. Access to electricity, access to adequate drinking water, acquisition of GRDP and government capital expenditure are variables that have a significant impact on the poverty rate (P0). Access to sanitation and population are not variables that affect the level of poverty (P0). The managerial implications of the government prioritize increasing district/city GRDP to reduce poverty.